A work study on Waters Unlimited, Inc. (Makers of Manila Pure Distilled Drinking Water) - Catibog, Anastacia Eliza M. (College of Engineering, 1997)
Water Unlimited, Inc., makers of Manila Pure Distilled Drinking Water, started its operations in 1991. The group saw it fit to conduct a work study on the company because the bottled drinking water industry, a booming business enterprise nowadays, is an interesting topic for methods engineering due the complexity of the processes involved in manufacturing the said product. The group focused on the production of 350 ml bottled distilled drinking water because it has the highest demand among the sizes being produced by the plant, it is characterized by continuous production and it involves labor intensive operations. The processes involved in the production of the said type are bottle making, labeling, cleansing (ozonation, filtration and distillation), filling, capping, sealing and packaging. Aside from the product and the operations, the study also tackled the production scheduling, the multistory plant layout, the material flow (procurement, external and internal transportation, and inventory control), the working conditions (working premises, plant services and production equipment) and the systems and procedures of the company. The company's organization is divided into the management and administration, the sales and marketing department, the production and operations department, the purchasing department, the quality control department and the maintenance department. From the detailed documentation, the core problems in the plant were identified, namely : inefficient packaging operation, inefficient machine maitenance and inefficient production planning. Other areas of concern, such as the absence of a research and development arm in the company, were also noted. Recommendations were proposed by the group regarding the plant's packaging procedure, supported by work measurement and time study. Meanwhile, the other problem areas, due to the study's scope and limitations and the time constraint, were set aside from further studies.